(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Cybersecurity is a critical concern in today’s digital age, with organizations and individuals facing an ever-evolving landscape of cyber threats. This paper provides a comprehensive review of cybersecurity threats, vulnerabilities, countermeasures, and future trends. It begins with an overview of prominent cybersecurity threats, including malware, phishing, and Distributed Denial of Service (DDoS) attacks, highlighting their impact on systems and data. The discussion then shifts to cybersecurity vulnerabilities, focusing on software vulnerabilities and human factors, such as human error and social engineering attacks. The paper also explores cybersecurity countermeasures, such as antivirus software, firewalls, and encryption, detailing how these tools work and their limitations. Furthermore, it examines emerging trends in cybersecurity, including new types of cyber attacks and advancements in cybersecurity technologies, and discusses their potential implications for cybersecurity professionals. By understanding the current cybersecurity landscape and anticipating future trends, organizations and individuals can better prepare for and mitigate the risks posed by cyber threats.